If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5b + -3) + -2(2b + 2) = -5 Reorder the terms: (-3 + 5b) + -2(2b + 2) = -5 Remove parenthesis around (-3 + 5b) -3 + 5b + -2(2b + 2) = -5 Reorder the terms: -3 + 5b + -2(2 + 2b) = -5 -3 + 5b + (2 * -2 + 2b * -2) = -5 -3 + 5b + (-4 + -4b) = -5 Reorder the terms: -3 + -4 + 5b + -4b = -5 Combine like terms: -3 + -4 = -7 -7 + 5b + -4b = -5 Combine like terms: 5b + -4b = 1b -7 + 1b = -5 Solving -7 + 1b = -5 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 1b = -5 + 7 Combine like terms: -7 + 7 = 0 0 + 1b = -5 + 7 1b = -5 + 7 Combine like terms: -5 + 7 = 2 1b = 2 Divide each side by '1'. b = 2 Simplifying b = 2
| 5x-(4x+4)=1 | | -x+13=x+5 | | x+13=x+5 | | -x^2+x-6=0 | | x^2+16x+62=0 | | (x-2)(x-4)=(x-3)(x+6) | | 64x^2+9=-48x | | 4y=8x-3 | | x^2+14x+46=0 | | (x+3)=7 | | x^2+30x=0 | | x^2+6x-55=0 | | (x-4)(x-4)=16 | | 4x^2=324 | | 1.25(5a-10)=-1.5a | | 24x^2+59x+36= | | 64x^2+47x+9=0 | | 2x(x+3)=-1 | | -2.46j-15=-12.54 | | (18x^3+14x^2+10x)= | | 10+10=20 | | -3(2+-4)+11=-7 | | 46.0365=7.3g+46 | | 16.6=0.8x-17 | | 88.7a-15=19.583 | | 20=z+23 | | 20=2+23 | | 0.6w+6=23.4 | | -[6z-(15z+10)]=10+(8z+8) | | y+8=-2 | | (2x+3)(3x+2)=(x-5)(6x+1) | | 34n=612 |